LEARNING A PROGRAMMING LANGUAGE BY INTEGRATING GENERATIVE ARTIFICIAL INTELLIGENCE - Kerimbayev Н.Н.; Menlibay Ж.Г. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This article discusses the theoretical foundations and practical aspects of the use of generative artificial intelligence technologies as a pedagogical tool in teaching programming. The importance of artificial intelligence in education is growing, and GenAI allows students to increase their motivation to learn, personalize learning materials and develop their practical skills. The article analyzes the main methods, advantages and limitations of integrating artificial intelligence into the educational process. During the research, artificial intelligence tools were used to automate and personalize the learning process. In particular, in the process of students mastering the basics of programming, artificial intelligence was used as a tool to help give dynamic feedback, interpret algorithms and correct errors. In addition, ethical issues and the impact of technology on the quality of education were discussed. The article provides practical recommendations for improving the effectiveness of the use of artificial intelligence in programming courses. This research will contribute to the introduction of innovations in the field of education and the discovery of new opportunities for using artificial intelligence tools. This approach is based on improving the quality of programming education and developing students’ creative and technical skills.